2002
DOI: 10.1002/psc.396
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and biological properties of the seven alanine‐modified analogues of the marine cyclopeptide hymenamide C

Abstract: The synthesis and biological activity of the marine cyclopeptide hymenamide C(1), showing an inhibitory effect on human neutrophil elastase degranulation release, were recently described. Based on this result, it was decided to undertake a systematic structure-activity relationship study of this cyclopeptide, based on the Ala-scan technique, in order to obtain useful information for the rational design of additional analogues. The synthesis and characterization of the seven Ala modified analogues are reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2006
2006

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Although hymenamide C inhibition of human neutrophil degranulation (IC 50 =18 μM) was not particularly impressive, the authors noted that cyclosporine, a clinically used immunosuppressive cyclopeptide, exerted "weaker inhibitory effect on elastase release". A structure-activity relationship study completed with this cyclopeptide concluded a "non-receptorial mode of action" for hymenamide C and its synthetic analogs (Napolitano et al, 2002). Dal Piaz et al (2002) reported an extensive investigation of the mechanism of phospholipase A 2 (PLA 2 ) inactivation by the novel marine sesterterpene petrosaspongiolide M (60), a bioactive sesterterpene isolated from the marine sponge Petrosaspongia nigra.…”
Section: Anti-inflammatory Compoundsmentioning
confidence: 99%
“…Although hymenamide C inhibition of human neutrophil degranulation (IC 50 =18 μM) was not particularly impressive, the authors noted that cyclosporine, a clinically used immunosuppressive cyclopeptide, exerted "weaker inhibitory effect on elastase release". A structure-activity relationship study completed with this cyclopeptide concluded a "non-receptorial mode of action" for hymenamide C and its synthetic analogs (Napolitano et al, 2002). Dal Piaz et al (2002) reported an extensive investigation of the mechanism of phospholipase A 2 (PLA 2 ) inactivation by the novel marine sesterterpene petrosaspongiolide M (60), a bioactive sesterterpene isolated from the marine sponge Petrosaspongia nigra.…”
Section: Anti-inflammatory Compoundsmentioning
confidence: 99%